2017
DOI: 10.1017/cem.2017.339
|View full text |Cite
|
Sign up to set email alerts
|

CAEP 2016 Academic Symposium: How to have an impact as an emergency medicine educator and scholar

Abstract: We describe a unique set of recommendations to develop educators who will influence EM, derived from a consensus from the EM community. EM leaders, educators, and aspiring educational scholars should consider how to implement this guide towards enhancing our specialty's educational mission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…These include ongoing mentorship opportunities, developing a community of practice, and having protected time for educators at every emergency medicine department. 17 The academic advancement of CEs is reported as slower than other academic tracks, 18 and the cause for this is likely multifactorial. 19 First, the focus for academic promotion remains on traditional measures such as quantity of papers and grant funding, with less academic reward for teaching and educational innovations.…”
Section: Discussionmentioning
confidence: 99%
“…These include ongoing mentorship opportunities, developing a community of practice, and having protected time for educators at every emergency medicine department. 17 The academic advancement of CEs is reported as slower than other academic tracks, 18 and the cause for this is likely multifactorial. 19 First, the focus for academic promotion remains on traditional measures such as quantity of papers and grant funding, with less academic reward for teaching and educational innovations.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 We found that PEM has a presence in patient care and teaching at 14 of the 17 Canadian medical schools. While university status varies across the country, sites are involved in teaching: undergraduate clerkship programs (8), RCPSC residency programs for PEM (10), off-service residents (14), fellowships (10), and CPD (7). Education scholarship is becoming established, with some sites providing salary support for this endeavour.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] The follow-up from the 2016 CAEP Academic Symposium on education entitled Emergency Physician Educators & Scholars … the Path to Success provided recommendations for training career educators, making an impact on education, and having scholarly work published. [5][6][7] The variability in infrastructure, support, and productivity for EM research programs across Canada was discussed at the 2014 CAEP Academic Symposium on research, at which recommendations were published to improve research funding, resident research supports, and training for career researchers. [8][9][10][11] Its 2017 follow-up symposium focused on recommendations to improve research through engagement, implementation, and knowledge translation (with published recommendations released in 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Impact as an education scholar requires formal training and mentorship. 6 This training can include a graduate degree, fellowship, or the new Royal College Area of Focused Competence Clinician Educator program. CAEP has supported the development of education scholars via the Clinician Educator Mentorship Service at the CAEP Annual Conference, the Academic Section Education Consultation Service for Divisions and Department of EM, and a second Academic Symposium on education scholarship in 2016.…”
Section: The Present: We've Come a Long Way In Just 8 Yearsmentioning
confidence: 99%
“…CAEP has supported the development of education scholars via the Clinician Educator Mentorship Service at the CAEP Annual Conference, the Academic Section Education Consultation Service for Divisions and Department of EM, and a second Academic Symposium on education scholarship in 2016. Building on the inaugural symposium, the 2016 symposium produced consensus guidelines on the training of future clinician educators, 7 the development of educators and scholars with an impact on EM, 6 and provided further guidance on the production of high quality medical education scholarship. 1,[8][9][10][11] These consensus guidelines suggest best practices to support the growth of the next generation of scholars.…”
Section: The Present: We've Come a Long Way In Just 8 Yearsmentioning
confidence: 99%